Demographic studies of owned dogs in the Northern Peninsula Area, Australia, to inform population and disease management strategies. Issue 12 (26th November 2018) - Hudson, EG; Brookes, VJ; Ward, MP
Abstract : Objective: To generate domestic dog demographic information to aid population and disease management in the Aboriginal and Torres Strait Islander communities of the Northern Peninsula Area, Queensland, Australia. Methods: Sight–resight surveys using standard and modified methods were conducted to estimate the free‐roaming dog population size. A cross‐sectional questionnaire of dog owners was used to gather dog demographic information and investigate owners' dog management behaviours. A survey was also conducted to estimate the total dog population size. Results: The mean total dog population size was estimated to be 813 (range, 770–868). The roaming dog population was 430 or 542 (95% confidence interval (CI) 254–608; 95% CI 405–680, standard and modified methods, respectively). Therefore, the roaming population represents 52.8% or 66.7% of the total population based on the sight–resight methodology. We surveyed 65 dog owners who owned 165 dogs (1 : 1 ratio of male : female dogs). Only 14% (95% CI 9–19) of dogs were sterilised and significantly more males were entire (P = 0.02). Although most dogs were pets (65%), hunting dogs were significantly more likely to be taken outside of the resident community (P < 0.001). The birth rate was 2.4 puppies/dog‐owning house/year, which was higher than the death rate (1.7 dogs/dog‐owning house/year). In the previous 12 months, 90% of the 109 deaths were dogs aged 0–2 years old. Conclusion: This study demonstrated that most of the dog population in the NPA is free‐roaming and that the population has increased, likely because of a lack of population management strategies such as sterilisation. This information will be used to develop population and disease management strategies in the NPA.